2006
DOI: 10.1111/j.1365-2036.2006.02805.x
|View full text |Cite
|
Sign up to set email alerts
|

Diverticular disease and migration – the influence of acculturation to a Western lifestyle on diverticular disease

Abstract: SUMMARY BackgroundDiverticular disease of the colon is more common in the Western world, compared with non-Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
2
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 20 publications
(23 reference statements)
3
52
2
9
Order By: Relevance
“…5,6 It is highly prevalent in western countries, but is rarely encountered in the developing world. 7,8 The risk of acquiring the disease increases uniformly with age, with approximately 40% of people aged over 60 years being affected in western countries. 9 Although most people with colonic diverticulosis remain asymptomatic, about 25% will eventually present with an episode of acute diverticulitis (the principal inflammatory complication of diverticulosis); of these, 15% will develop other significant and often serious complications such as abscess, fistula or perforation.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 It is highly prevalent in western countries, but is rarely encountered in the developing world. 7,8 The risk of acquiring the disease increases uniformly with age, with approximately 40% of people aged over 60 years being affected in western countries. 9 Although most people with colonic diverticulosis remain asymptomatic, about 25% will eventually present with an episode of acute diverticulitis (the principal inflammatory complication of diverticulosis); of these, 15% will develop other significant and often serious complications such as abscess, fistula or perforation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, "non western" immigrants showed a lower risk of DD-related hospital admissions and death but after adjusting for age, risk increased with years of residence in Sweden [13] . In contrast, other studies found no changes in DD incidence amongst migrant communities following periods of naturalization in countries with high or low risk DD in the native population.…”
Section: Epidemiology and Public Health Impactmentioning
confidence: 99%
“…Diverticulosis increases with age; it is estimated less than 10% in those under the age of 40 and increases to 65-70% in those above 65 years of age [3][4][5]. Besides diverticulosis, the prevalence of colon cancer is also increasing in the western world [3,6]. Colorectal cancer is a leading cause of cancer mortality in the Western world, with more than 1,000,000 new cases per year and with 500,000 deaths per year worldwide [7].…”
Section: Introductionmentioning
confidence: 99%